Ventromedial prefrontal volume predicts understanding of others and social network size. - Lewis, P; Rezaie, R; Brown, R; Roberts, N; Dunbar, R (2011)
Cognitive abilities such as Theory of Mind (ToM), and more generally mentalizing competences, are central to human sociality. Neuroimaging has associated these abilities with specific brain regions including temporo-parietal junction, superior temporal sulcus, frontal pole, and ventromedial prefrontal cortex. Previous studies have shown both that mentalizing competence, indexed as the ability to correctly understand others' belief states, is associated with social network size and that social group size is correlated with frontal lobe volume across primate species (the social brain hypothesis). Given this, we predicted that both mentalizing competences and the number of social relationships a person can maintain simultaneously will be a function of gray matter volume in these regions associated with conventional Theory of Mind. We used voxel-based morphometry of Magnetic Resonance Images (MRIs) to test this hypothesis in humans. Specifically, we regressed individuals' mentalizing competences and social network sizes against gray matter volume. This revealed that gray matter volume in bilateral posterior frontal pole and left temporoparietal junction and superior temporal sucus varies parametrically with mentalizing competence. Furthermore, gray matter volume in the medial orbitofrontal cortex and the ventral portion of medial frontal gyrus, varied parametrically with both mentalizing competence and social network size, demonstrating a shared neural basis for these very different facets of sociality. These findings provide the first fine-grained anatomical support for the social brain hypothesis. As such, they have important implications for our understanding of the constraints limiting social cognition and social network size in humans, as well as for our understanding of how such abilities evolved across primates.